Perlindungan Hukum bagi Pekerja Perempuan yang Mengalami Diskriminasi dalam Hubungan Kerja - Melia Dwi Hasanah; Dea Zulfa Inayah; Nazwa Bunga Rezki Perdana Lubis; Cindy Aulia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study uses a qualitative method to examine legal protection for female workers who experience discrimination in employment relationships. Discrimination against women in the workplace remains prevalent, taking forms such as unequal pay, limited opportunities for promotion, and sexual harassment, all of which affect their safety and comfort at work. Legal protection for female workers is regulated by various laws, including the Manpower Act, the Human Rights Act, and ILO conventions ratified by Indonesia. However, the implementation of these protections is often ineffective due to weak law enforcement, limited awareness among female workers regarding their rights, and the persistence of patriarchal culture. This study aims to analyze the extent to which legal regulations and their implementation function effectively, as well as the obstacles female workers face in claiming their rights. Data were collected through in-depth interviews, literature review, and document analysis. The findings indicate the need to strengthen labor inspection institutions and provide legal education for female workers to achieve justice in employment relationships.